2023
DOI: 10.1044/2022_ajslp-22-00099
|View full text |Cite
|
Sign up to set email alerts
|

Developing Social-ABI-lity: An Online Course to Support Safe Use of Social Media for Connection After Acquired Brain Injury

Abstract: Purpose: People who have an acquired brain injury (ABI) experience challenges using social media. Inversely, rehabilitation clinicians report feeling inadequately prepared to support them in its use. We aimed to develop a collaboratively designed, evidence-based online training resource to support people with an ABI to learn about using social media. Key recommendations for course design have previously been identified through a mixed methods approach, including (a) qualitative exploration of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Findings from this proof-of-concept study (Brunner et al, 2022a) indicated that the social-ABI-lity course was acceptable and engaging for the participants, and that some aspects of social media communication skills for people with an ABI could be trained through an online, self-directed course. However, its efficacy as a standalone treatment is yet to be determined.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Findings from this proof-of-concept study (Brunner et al, 2022a) indicated that the social-ABI-lity course was acceptable and engaging for the participants, and that some aspects of social media communication skills for people with an ABI could be trained through an online, self-directed course. However, its efficacy as a standalone treatment is yet to be determined.…”
Section: Introductionmentioning
confidence: 93%
“…The CyberABIlity training programme (Monash University, 2022) provides free online training for people with ABI to learn specifically about cybersafety, including identifying and navigating cyberscams. The self‐directed online course, ‘social‐ABI‐lity’, focuses on successful use of social media after ABI (Brunner et al., 2022a). This course was developed through a collaborative design process with participants with ABI, family members and clinicians, and tested through a proof‐of‐concept study with four participants with ABI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This program enables people to progress through seven modules about conversations after brain injury, record and reflect on conversations to learn and see progress, get feedback from their speech pathologist as they practice and connect to video calls with their speech pathologist. The Toolkit programs have shown promising feasibility and acceptability in pilot studies (Avramović et al, 2023;Brunner et al, 2022Brunner et al, , 2023 and are currently being expanded to include virtual reality components, as well as starting to be adapted for non-English contexts. The Social Brain Toolkit has already gained industry and clinical adoption in Australia, the United States, and the United Kingdom, with over 2500 users accessing the self-guided courses (freely available at https://abi-communicationlab.sydney.edu.au/social-brain-toolkit/).…”
Section: Investigating Translation From Research To Practicementioning
confidence: 99%
“…29 It could include educational (e.g., information sessions), behavioural (e.g., self-monitoring), or supportive (e.g., phone coaching) dimensions. 29 These tools are varied and may include mobile health support applications, 30,31 telerehabilitation, 32 online resources, 33 biofeedback, 34 or wearable sensors and machine learning. 35 Some of these technologies can also be smart by "dynamically access[ing] information, connect[ing] people, materials […] in an intelligent manner" (p. 62).…”
Section: Introductionmentioning
confidence: 99%